2018
DOI: 10.1055/s-0038-1669943
|View full text |Cite
|
Sign up to set email alerts
|

Mermaid Syndrome: A Case Report of a Rare Congenital Anomaly in Full-Term Neonate with Thumb Deformity

Abstract: The mermaid syndrome (sirenomelia) is an extremely rare anomaly, an incidence of 1 in 100,000 births, in which a newborn born with legs joined together featuring a mermaid-like appearance (head and trunk like humans and tail like fish), and in most cases die shortly after birth. Gastrointestinal and urogenital anomalies and single umbilical artery are clinical outcome of this syndrome. There are two important hypotheses for pathogenesis of mermaid syndrome: vitelline artery steal hypothesis and defective blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…There have been a few reported sirenomelia cases to non-diabetic mothers, indicating that no definite cause can be attributed to these cases 5. Sirenomelia’s correlation to maternal age younger than 20 and older than 40 years has also been noted implying that extremities in age may be an important risk factor 6 7…”
Section: Discussionmentioning
confidence: 93%
“…There have been a few reported sirenomelia cases to non-diabetic mothers, indicating that no definite cause can be attributed to these cases 5. Sirenomelia’s correlation to maternal age younger than 20 and older than 40 years has also been noted implying that extremities in age may be an important risk factor 6 7…”
Section: Discussionmentioning
confidence: 93%
“…За даними різних джерел, ця вада зустрічається з частотою 0,98-1 на 100 000 новонароджених [5,9]. Сиреномелія характеризується повним або частковим злиттям нижніх кінцівок, вадами сечо-видільної системи, відсутністю зовнішніх статевих органів, наявністю імперфорованого анусу, тощо [9,14]. У зв'язку із рідкістю даної вади, наводимо власне спостереження.…”
Section: клінічний випадокunclassified
“…11 Limited studies reported hemodynamic changes associated with phototherapy, such as it can lead to the reduction in left ventricular stroke volume in newborn and premature infants. 12 Also, an increase in the left pulmonary artery flow has been reported in term neonates, whereas reduced brain blood flow and decreased renal flow have been stated in premature births. 13 Therefore, the aim of this study was to assess changes in total stroke volume in infants who undergo phototherapy for jaundice.…”
Section: Introductionmentioning
confidence: 99%